The effects of the FIFA 11+ and 11+ Kids training on injury prevention in preadolescent football players: A systematic review - Yalfani, A.; Saki, F.; Kerman, M. T. (Annals of Applied Sport Science, 2021)
Background: Most football players (58%) around the world are younger than 18 years and almost three quarters of these young players are under the age of 14 years old. The characteristics of football injuries in children aged 7 - 12 years old are different from those of the young and adult players. Objectives: The aim of this systematic review was to evaluate effects of FIFA 11+ and 11+ Kids warm-up programs in preventing the injuries on the pre-adolescents football players. Methods. PubMed and Science Direct databases were used using the search terms including FIFA 11+, 11+ kids, injury prevention, football, and pre-adolescent. A total of 520 studies were identified, of which 10 met the inclusion criteria of the review. Methodological quality of the studies were assessed through the PEDro score. Results: The 11+ Kids exercises reduce the injury and improve the physical fitness factors such as balance, jumping activities and lower limb isokinetic strength. Although 11+ exercises are designed for players aged over 14 years, they result in an improvement in movement patterns, stability, and trunk muscle endurance. The methodology quality of the randomized studies was in the range of 4 to 7 (out of 10) and the mean score of the studies was obtained 5.6, indicating moderate quality of the methodology. Conclusion: 11+ program alone or in a combination with the newly-developed 11+ Kids program may be helpful in preventing the injury and improving the performance, especially if implemented for a longer period or with more exercise sessions per week.